Educating nurses on prioritization: insights from a mixed-methods study on unfinished nursing care - Erika Bassi; Terry L. Jones; Stefania Chiappinotto; Daniela Tartaglini; Alberto Dal Molin; Alvisa Palese (BMC Nursing)
Abstract Background Several factors increasing or minimizing the occurrence of Unfinished Nursing Care (UNC) have been documented to date. However, evidence available suggests a sort of stability in the decision-making patterns influencing the occurrence of UNC indicating the need to deepen the underlying criteria also to inform changes in nursing education. Methods A sequential, explanatory, mixed-methods study design was performed including a cross-sectional survey and a qualitative descriptive study. The quantitative phase consisted of a national survey involving 15 hospitals, 110 units, and 1,977 nurses invited to complete the Unfinished Nursing Care Survey (from 1 ‘never’ to 5 ‘always unfinished’). A subsequent qualitative phase involved three focus groups with nurses identified from hospitals with high, medium, and low UNC occurrence. The data integration at the findings level was performed by using the explaining joint technique, where qualitative findings were used to explain the data collected in the quantitative phase. The Good Reporting of a Mixed-Methods Study guideline was followed. Results A total of 1,400 nurses (70.8%) reported that the incidence of UNC ranged from 1.92 out of 5 (SD = 0.31) to 2.48 (SD = 0.32). One theme emerged from the focus groups, namely “The rules of engagement” and four sub-themes reflecting the priority criteria affecting UNC: (1) “Addressing biomedical needs”; (2) “Physicians’ expectations come first”; (3) “Signing for/audited activities”; and (4) “It depends; human dignity counts”. After data integration, a thematic relationship emerged, confirming that the prioritization criteria underlying the UNC pattern matched the elements of care most frequently withheld by nurses in daily practice. Conclusions Overall, priorities are set according to certain rules that prompt nurses to decide what should come first and what can be left unfinished or postponed. Four criteria have emerged: two related to biomedical patient needs and physician-centered workflow expectations, one related to organizational expectations and rules, and one related to nursing as a discipline. Nursing educators should consider these findings when designing curricula. In addition to providing sound theoretical education in the fundamentals of nursing, it is recommended that clinical placements be offered in supportive work environments where students are empowered to prioritize activities related to their scope of practice. Clinical trial number Not applicable.